PENINGKATAN HASIL BELAJAR PKn MELALUI MODEL PEMBELAJARAN DIRECT INSTRUCTION PADA SISWA KELAS II SD INPRES NIPA-NIPA KOTA MAKASSAR - Amran, Arini; Muhammadiah, Mas’ud; Arsyad, Susalti Nur (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The research was to describe the Direct Instruction Method for Increasing Of study result Nationality Learning sub title environment treatment in Elementary School of Nipa-Nipa Makassar.Type of this research was Classroom Ation Research which based on several steps, such as planning, action implementation observation, evaluation, and reflection. Subject of the research were II class students SD Inpres Nipa-Nipai Makassar as many as 27 students. Data collection used observation and the next test analyzed by descriptive method. The result of the research showed that the Direct Instruction Method could improve learnig result of students in II class SD Inpres Nipa-Nipa Makassar. In this case based on the improvement average value of learning result from 54.23% in cycle I became 78.63% in cycle II and the increase of average value is eleven percent. So, this research is considered successful on minimal criteria completeness from 34% at cycle I to 81% at cycle II.